Gadamer's repercussions : reconsidering philosophical hermeneutics - Krajewski, Bruce, 1959- (University of California Press, 2004)
German philosopher Hans-Georg Gadamer influenced the study of literature, art, music, sacred and legal texts and medicine. This volume brings together many prominent scholars to assess, re-evaluate and question Gadamer's works, as well as his place in intellectual history.
Keywords: Gadamer, Hans-Georg, -- 1900-2002.; Gadamer, Hans-Georg, -- 1900-2002; PHILOSOPHY -- History & Surveys -- Modern.; PHILOSOPHY -- Political.